Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Countries. (Policy Papers; Policy Paper ;, 2017)
PRGT-related policies following the 2015 enhancement of the financial safety net for LICs, while options to better assist countries confronting sudden balance of payments needs due to large natural disasters are under consideration. Demand for PRGT resources has increased. Demand for concessional resources has exceeded historical averages in recent years, mainly in response to sustained low commodity prices and deteriorated global financial market conditions. Demand is expected to reach new highs in 2017 and longer-term estimates have been raised somewhat.